Locating state: perspectives of governance and development in India - Singh, Shyam (2010)
Recently, we have witnessed a massive economic slow down with sever negative effects on the developing and developed economies. This development created a very inconvenient and impractical situation in accepting an adage of neo-liberalism that the absence of state and the dominance of market would lead the human development in true sense, or civil society which is now connecting itself with the market thinking can provide remedial to the problem. Therefore, the hope of re-visit of state-led democratic governance with a hold on economic and human development gets fuel to sideline the neo-liberal posture. Paper presents a comparative analysis among all the paradigms of development i.e. state, market and civil society and discusses that which paradigm is best suitable for developing economies like India. - Reproduced.
Keywords: Public administration - India; Public administration